(untitled) (Economic and Political Thought, 2013)
One of the most important topics of 2011–2013 concerning the European Union and its finances was the Multiannual Financial Framework 2014–2020. Its negotiations and the outcome will have a great influence on all the next 7 years for all 28 countries of the Union and their citizens. The impact of the new MFF will be easy to recognize in the economic possibilities, in the structure and issues of internal and external European policies. The main concern of this paper is an answer to a question regarding Polish expectations in connection with the new budgetary framework as well as a closer look on the involvement of our country in the long negotiation process. The first part of the article concerns the Polish national priorities in view of the MFF 2014–2020, which are the cohesion policy and the Common Agricultural Policy funds. They are described along with their current objectives, challenges and main beneficiaries. The Polish participation in the ongoing process of the MFF adoption is the main subject of the second part of the paper. The Polish government, the opposition, Polish Euro-parliamentarians and employees of other European institutions as well as the Polish society – all exert certain influence on the final outcome of the MFF 2014–2020.